Effect of climate on the incidence of oestrus, conception and cycle length in Murrah buffaloes - Reddy, A Obi; Ramesha, K P; Rao, M K (The Indian Journal of Animal Sciences, 2012)
Information on 4 369 oestruses was analyzed to study effect of climate on the incidence of oestrus, conception rate and length of oestrus cycle. Maximum percentage of heats (11.44) were noticed in November and minimum (5.97) in June. Among seasons the monsoon accounted for 37.42% of heats, while winter and summer accounted for 36.55 and 26.02% respectively. When oestruses were grouped depending upon the time of heat detection, 31.79% were detected during coldest period of the day (0-4 hr), followed by 24.20% during the period 4-8 hr and the lowest (3.39%) during 16-20 hr period. The conception rates were more or less similar for heats detected during different periods of the day, and they varied between 36.69 and 39.80%. Among months, conception rate was the lowest during April (29.45%), while it was the highest in September (44.84%). The conception rates ranged from 41,85 to 44.85% during August to November and they were 29.45 to 32.92% for February to April. The average oestrus cycle length was 33.44 days and it ranged from 30.59 days following oestruses in September to 41.06 following oestrus in April. On the whole in more than 21 % of the cases the cycle length exceeded 67 days indicating the need for strengthening heat detection measures so as not to miss heats and improve the reproductive efficiency.